The Crime of Trafficking in Human Organs through the Information System: Comparative study (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
Crimes no longer occur in their simple traditional form, as the development of human societies contributed to the development of crime and the creation of crimes that were not known before, and among these crimes is the crime of trafficking in human organs through the information system, which is one of the crimes that aided technical progress in the field of communications, information technology and the field of modern medicine to spread it; Organized criminal gangs took advantage of the facilities resulting from the development of information and communication technology to trade in human organs, which contributed to the creation of an electronic black market for human organs mafia gangs. The importance of this study stems from the fact that it is different from traditional crimes and is one of the issues emanating from technological progress and the development of organized crime.The study aims to clarify the provisions of the crime of trafficking in human organs through the information system, according to the comparative approach between the Saudi system and the UAE law. The results of the study showed that the Saudi regulator did not explicitly stipulate human organ trafficking in the cybercrime system, but was implicitly included as a form of criminal behavior for the crime of human trafficking in the Saudi human trafficking crime system, unlike the UAE law, which stipulates organ trafficking alongside human trafficking. According to the Saudi system, this crime is considered electronic if it occurs through the information network or a computer. In light of its results, the study concluded the following recommendations:1.  The Saudi cybercrime system explicitly provides for the criminalization of electronic trafficking in human organs as one of the forms of cybercrime, similar to its counterpart in UAE law.2.  Community awareness of the seriousness of this crime, the speed with which it is being investigated via the Internet, the ease with which offenders attract individuals, and financial reward for those who report or contribute to the commission of this crime.